Wybrane elementy marketingu wyborczego, jako determinant decyzji wyborczych elektoratu w trakcie kampanii wyborczych - Widera, Zbigniew (Political Preferences, 2011)
Selected elements of election marketing as a determinant of the decision of the electora- te during the electoral campaign.Voter deciding who cast his vote, is determined of different factors. They include both acquired value systems, the impact of the environment in which the voter is located as well as the political state of the market at the time of the election. It comes to e.g general and local socio - economic situation. Knowing, how detrminanes are shaping up electoral decision not only allows policy-makers respond appropriately to the needs of the electorate but also to streamline the techniques and instruments for electoral marketing.